2007
DOI: 10.1177/0267323107073746
|View full text |Cite
|
Sign up to set email alerts
|

How States, Markets and Globalization Shape the News

Abstract: This article presents a comparative content analysis of the US and French national press in the 1960s and 1990s to test hypotheses about the influence of media structure on journalistic discourse. The US and French press are presented as strongly contrasting models, with the US press more commercialized, and the French press more closely tied to the political field. Using a variety of story- and paragraph-level content indicators, this studyshows that the French press ( Le Monde and Le Figaro) offers relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 13 publications
8
99
1
6
Order By: Relevance
“…This aspect of interventionism differs from journalistic intervention in the form of interpretation, because it includes a reference to the journalist's explicit personal perspective. In contrast, an interpretative style entails the explanation of a fact, without necessarily including a value judgment (Benson and Hallin 2007). This dimension closely resembles the "watchdog role" (Weaver and Wilhoit 1996).…”
Section: Conflict Frames Depend On Journalistic Interventionismmentioning
confidence: 99%
“…This aspect of interventionism differs from journalistic intervention in the form of interpretation, because it includes a reference to the journalist's explicit personal perspective. In contrast, an interpretative style entails the explanation of a fact, without necessarily including a value judgment (Benson and Hallin 2007). This dimension closely resembles the "watchdog role" (Weaver and Wilhoit 1996).…”
Section: Conflict Frames Depend On Journalistic Interventionismmentioning
confidence: 99%
“…In addition, their comparative analysis of American and French news organizations found that on the aforementioned situations, the US media strongly relied more on the political authorities than the French ones. As far as 'Arab Spring' is concerned, Bruce (2014) proved the findings of Benson & Hallin (2007), which suggest that in times of unrest the western media outlets tend to rely more on the political authorities. Furthermore, many reporters described the Egyptian 'Arab Spring' as a story of civil unrest.…”
Section: Methodsmentioning
confidence: 81%
“…This finding depends on the results of the other researchers of the field (Benson & Hallin, 2007;Bruce, 2014). Meanwhile, the Chinese news outlet was the only one that contained an economic framed news story.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations